Докажи тождество:
(3a + b) 3 - (а + 3b)3 – 18ab(a - b) = 26(а3
– b3)​

сьдвщы сьдвщы    2   17.03.2021 11:30    0

Ответы
Vgenika Vgenika  17.03.2021 11:40

Объяснение:

(3a + b) 3 - (а + 3b)3 – 18ab(a - b) = 26(а3

– b3)​

27a³+27a²b+9ab²+b³-(a³+9a²b+27ab²+27b³)-18a²b+18ab²=26a³-26b³

27a³+27a²b+9ab²+b³-a³-9a²b-27ab²-27b³-18a²b+18ab²=26a³-26b³

27a³+27a²b+9ab²+b³-a³-9a²b-27ab²-27b³-18a²b+18ab²=26a³-26b³

В левой части считаем и получаем

26a³-26b³=26a³-26b³

Тождество доказано

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра